Development of an experimental set-up for dynamic force measurements during impact and perforation, coupling to numerical simulations. (May 2016) - Zhong, W.Z.; Mbarek, I.A.; Rusinek, A.; Bernier, R.; Jankowiak, T.; Sutter, G.
Highlights: A specific device has been developed to define more quantities during perforation tests. Actually thanks to the new set-up, it is possible to define: The initial impact velocity V0. The residual velocity VR. The ballistic limit is reached VB. The global resistance force history F(t) and the resistance force evolution as function of the initial impact velocity F(V0 ). The failure pattern depending on the projectile shape. Abstract: Quasi-static tension and dynamic compression experiments on S235JR mild steel were performed using a screw-driven machine and a split Hopkinson pressure bar (SHPB) device. A wide range of strain rates from 10 −4 to 2500 s −1 has been covered during experiments. The Johnson–Cook constitutive relation was adopted to describe the material visco-plastic behaviour. Ballistic impact experiments on S235JR plates with conical-nose shaped projectile were carried out using pneumatic gas gun having different impact velocities varying from 49 to 181 m/s. A new experimental set-up allowing resistance force measurement during impact and perforation was developed. Different impact velocities and thicknesses were evaluated during ballistic experiments. All the projectiles are 12.8 mm in diameter and 28g in weight. The ballistic impact device is equipped with laser sensors for velocities measurements and piezoelectric sensors for dynamic force measurement. Based on numerical and experimental investigations, the ballistic properties and failure modes of the material have been studied. The finite element code ABAQUS/Explicit was used to simulate the perforation process but also to have a better understanding of the measurement. A good agreement between experiments and numerical results has been observed in terms of ballistic curves, failure patterns, resistance force as well as the energy balance.